Three ways to put a library card on a cell phone - Arroyo-Vázquez, Natalia (Anuario ThinkEPI, 2015)
Three solutions, along with their advantages and disadvantages, are shown to bring the library card to the smartphone: barcode reproduction, Passbook type applications, and NFC technology. Some are simple to implement and others more complex, but all are technically feasible and can be implemented immediately. The smart card concept, which provides a new avenue of communication between the library and the user, is also introduced. Finally, uses of iBeacons are explored.